Iron status in young elite athletes: Influence of diet, exercise and gender - Koehler,K.; Braun, H.; Achtzehn, S.; Predel, H. G.; Mester, J.; Schänzer, W. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Despite widespread research and education, iron still has to be considered as one of the most critical nutrients in public health as well as in exercise nutrition. The prevalence of iron depletion among athletes tends to be higher than in the general population. Additionally, there is sufficient evidence that suboptimal iron status may influence exercise capacity and/or sport performance. Hence, the present study was designed to identify the influences of gender, diet and exercise on iron status across a wide range of sports and levels of competition in young elite athletes. METHODS Diet, exercise and haematological data from 177 junior elite athletes (100 f, 77 m; 16.3 +- 3.0 y, 64.8 +- 13.5 kg, 174.3 +- 10.9 cm) from 32 different sports were analyzed retrospectively. Diet and exercise data were collected during seven days using a standardized and validated record. Following the recording period, fasting blood samples were obtained from the athletes. RESULTS Among all athletes, approximately 40 % had reduced serum ferritin levels. About 4 % of the athletes were anaemic. Female athletes had significantly more abnormal haematological values and consumed significantly less dietary iron, cobalamin (both p < 0.001) and folic acid (p < 0.01). Athletes with low ferritin levels indicative of iron depletion consumed significantly less meat and fish (p < 0.01) than athletes with regular levels. Female athletes with iron depletion had a significantly lower iron density in their diet (5.8 +- 0.9 vs. 6.5 +- 1.1 mg/1000 kcal, p < 0.01), which was not the case in male athletes. However, only in male athletes ferritin levels were significantly affected by practice duration and energy expenditure (p < 0.05). DISCUSSION There were a noticeable number of cases with low ferritin levels indicative of iron depletion among young elite athletes. Our results suggest that the interrelations between an athlete`s iron status and his/her diet and exercise regimen is affected by the athlete`s gender: in female athletes, iron depletion was more prevalent and serum ferritin levels were primarily affected by dietary iron density; in male athletes, energy expenditure and practice duration seemed to influence iron status strongly.